Les pays où l’on arrive toujours : territoires d’enfance et itinéraires rêvés - HENKY, Danièle (Ondina - Ondine, 2019)
André Dhôtel’s home country as Henri Bosco’s birthplace is a lively place. Culture, memories, feelings or dreams the author place there make of this space an original one. When we depict these spaces in « books intended for the youth » they describe both imaginary geography and imaginary history which overlap on the spatio temporal reality. By drawing from their memories and their imagination to describe the ideal destination towards which, in these novels, we set off, André Dhôtel and Henri Bosco, respectively in the Country where one never arrives and in the Child and the river, present either only a quest of country but a journey towards a territory which is used more as framework to an initiation than as framework to a nostalgic return to the beginning of life. Keywords: Journey to the native land / memories and imagination / spatiotemporal reality / initiatory quest / ideal destination